Revisiting the outstanding flooding episode of November 1967 in the greater metropolitan Lisbon area - Trigo, Ricardo M. (2018)
The deadliest storm affecting Portugal since, at least, the early 19th century, took place on the 25 and 26 November 1967 causing more than 500 fatalities. Here we provide a comprehensive multi-disciplinary assessment of this episode, including the main socio-economic impacts, particularly the numbers and location of victims (dead, injured, homeless and evacuated). Based on the sub-daily time series of a representative station, and its Intensity-Duration-Frequency curves, we have found that the exceptionality of this rainfall event is particularly linked to rainfall intensities ranging in duration from 4 to 9 hours compatible with return periods of 100-years or more. This range of time scale is similar to the estimated concentration time values of the hydrographic basins affected by the flash flood event. Most victims were sleeping or were caught by surprise at home in the small river catchments within the greater metropolitan Lisbon area. The majority of people who died or who were severely affected by the flood lived in degraded housing conditions often raised in a clandestine way, occupying flood plains near the stream beds. This level of destruction observed at the time is in stark contrast to what was observed in subsequent episodes of similar amplitude. In particular, since 1967 the Lisbon area, was struck by two comparable intense precipitation events in 1983 and 2008 but generating considerably fewer deaths and evacuated people.